Scale of Professional Beliefs of Physical Education Teacher - Maria Brudnik-Dąbrowska (University of Lower Silesia, 2012)
Scale of Professional Beliefs of Physical Education Teachers (SPB-PE) aims at measuring irrational beliefs associated with the professional role one fulfils. The paper presents consecutive stages of constructing the tool based on theoretical premises of Albert Ellis. The study has demonstrated a four-factor structure of the scale (ps1. ambition, perfectionism: N = 10, α=0,76; ps2. avoidance N = 8, α=0,69; ps3. expectation of respect N = 5, α=0,71; ps4. neuroticism N = 7, α=0,60).